Meta-analysis: The effect of means ends analysis learning model on students’ mathematical problem-solving ability - Khoiriyah, Himatun; siregar, Machrani Adi Putri (Desimal: Jurnal Matematika, 2023)
This study aimed to determine the effect of using the MEA learning model on improving students' mathematical problem-solving abilities. The MEA learning model is a model that teachers can use to improve students' problem-solving abilities. This research is meta-analytic, namely by collecting data from previous researchers and then finding the effect size of all the data that has been obtained. Many of the data points found that match this research have met the criteria when searched using Google Scholar with the specified keywords. This research analysis tool uses SPSS software version 29.0 and uses the Cohen formula in data analysis. The finding of the effect size of the entire data is 1.431, which is categorized as having a considerable influence. Based on moderator variable analysis, the number of samples with  showed a larger effect size than . Furthermore, based on the level of education of junior high school students, it has an effect size that is categorized as having a large influence. This meta-analysis study shows that using the MEA learning model affects students' mathematical problem-solving abilities.